2016
DOI: 10.2320/matertrans.e-m2016807
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of (100) Oriented Silicon and Nickel Silicide Nanocomposite Films Grown on Si on Insulator and Si on Quartz Glass Substrates

Abstract: We have grown (100) oriented composite lms of Si and Ni silicide nanocrystals (Ni-Si NC lm) on substrates of Si on insulator (SOI) and Si on quartz glass (SOQ). Owing to improvement of carrier transport properties and reduction of the thermal conductivity in the oriented lms, they have higher dimensionless gures of merit, ZT of 0.22-0.42 for p-type Ni-Si NC lm and 0.08-0.13 for n-type Ni-Si NC lm than that of bulk Si (ZT < 0.01) at 30 C. The ZT values of p-type and n-type Ni-Si NC lms were increased to 0.65 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In particular, twin defects [Fig. 4(c)] analogical to Ni-Si assembly 50) were also found, which was reasonable for enhancing phonon scattering and decreasing k.…”
Section: Low-dimensional Strategies Of Reducing-k-orientedmentioning
confidence: 65%
See 1 more Smart Citation
“…In particular, twin defects [Fig. 4(c)] analogical to Ni-Si assembly 50) were also found, which was reasonable for enhancing phonon scattering and decreasing k.…”
Section: Low-dimensional Strategies Of Reducing-k-orientedmentioning
confidence: 65%
“…49) Immediately after, they used silicon on insulator (SOI) and silicon on quartz (SOQ) as substrates for indicating the effects of different substrates on Ni-Si phase separation and the corresponding TE performance. 50) Studies shown that SOI and SOQ substrates generate more planar defects and twin defects in the film after annealing at 1200°C, which act as phonon scattering centers. The twin defects directly lead to lower k (2.8 W mK −1 ) than previous samples.…”
Section: Low-dimensional Strategies Of Reducing-k-orientedmentioning
confidence: 99%
“…132) A technique for calculating the temperature change and thermal effusivity at the tip of a probe and simultaneously mapping the Seebeck coefficient and thermal conductivity from spatial information on the potential difference has also been reported and is expected to be indispensable for evaluating the reliability of thermoelectric energy harvesters. 133,134) A thermoreflectance method has become a popular means of evaluating the thermal diffusivity and thermal conductivity of thin films. 135,136) One side of a thin film is instantaneously heated by pulsed light to detect the temperature response at a position a certain distance from the film.…”
Section: Major Challenges and Thermophysical Metrologymentioning
confidence: 99%
“…Previous studies showing the interesting role of the well defined orientations of nanoplates embedded in Si wafers on the transport properties of these nanostructured materials have been reported for nanocomposite thin films (Takashiri et al, 2018;Chen et al, 2020). Thus, the singular morphological and crystallographic characteristics of NiSi 2 nanocomposites in conjunction with well established silicon-based integrated circuit technology make them potential materials for developments of novel thermoelectric devices (Mingo et al, 2009;Uchida et al, 2013Uchida et al, , 2016Guo & Huang, 2015).…”
Section: Introductionmentioning
confidence: 96%